Metropolitan Governance for Territorial Cohesion - Pirlone, Francesca; Spadaro, Ilenia; Candia, Selena (TeMA - Journal of Land Use, Mobility and Environment, 2017)
This paper proposes and defines new metropolitan governance strategies for territorial cohesion between inland and urban areas. Different reflections are here presented to comprehend how is it possible to implement cities’ ability to understand and manage metropolitan dynamics. In Europe, urbanisation and land abandonment is a widespread phenomenon compared to many other parts of the world. According to research carried out by the European Union it is estimated that four out of five European citizens will be living in urban areas abandoning villages and rural areas. Many European metropolitan areas are character-rized by overpopulated centres, degraded suburbs and different abandoned or almost abandoned inland areas. These areas, if well connected among them and to the main metropolitan centre, can contribute to solving many urban challenges. There is the necessity to image metropolitan areas as a single entity to increase the cohesion of lands. The latent capital of inland areas can be considered as driving factor behind territorial cohesion and development. This paper analyses in deep the case of the Italian Metropolitan Cities proposing a new governance approach to increase the capacity of urban systems to adapt to natural and man-made changes, considering the hinterland as a strong point rather than a disadvantage. Strategic and Spatial Plans drive the growth of metropolitan areas in a competitive space-economy and support sustainable development policy by ensuring a balance between urban areas with strong competitiveness and inland areas.